Odpowiedzi

Najlepsza Odpowiedź!
2009-12-08T22:56:34+01:00
1]√3-(√3-1)²=√3-(3-2√3+1)=√3-3+2√3-1=3√3-4,,,,,,,,,,,,,,,,,,,,,,,,,, zad.2]=w licznik wpisz:12(√7+√3),,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,, w mianownik wpisz:(√7-√3)(√7+√3)=7-3=4,,,,,,,,,,,,,,,,,,,,,,,,,,,,, w liczniku masz12 i ono skróci sie z mianownikiem i zostanie liczba=3(√7-√3) pozdrawiam
2009-12-08T22:58:45+01:00
√3-(√3²-2√3+1)=√3-3+2√3-1=3√3-4

12(√7+√3) 12(√7+√3) 12(√7+√3)
_______________ =______________ =____________ = 3√7+3√3
(√7-√3) (√7+√3) √7²-√3² 4